Raman and FTIR Studies on PECVD Grown Ammonia-Free Amorphous Silicon Nitride Thin Films for Solar Cell Applications. (26th May 2013) - Ahmed, Nafis; Singh, Chandra Bhal; Bhattacharya, S.; Dhara, S.; Bhargav, P. Balaji
Abstract : Ammonia- (NH3 -) free, hydrogenated amorphous silicon nitride (a-SiN x :H) thin films have been deposited using silane (SiH4 ) and nitrogen (N2 ) as source gases by plasma-enhanced chemical vapour deposition (PECVD). During the experiment, SiH4 flow rate has been kept constant at 5 sccm, whereas N2 flow rate has been varied from 2000 to 1600 sccm. The effect of nitrogen flow on SiN x :H films has been verified using Raman analysis studies. Fourier transform Infrared spectroscopy analysis has been carried out to identify all the possible modes of vibrations such as Si–N, Si–H, and N–H present in the films, and the effect of nitrogen flow on these parameters is correlated. The refractive index of the above-mentioned films has been calculated using UV-VIS spectroscopy measurements by Swanepoel's method.